Total Quality Manajement (TQM) Kepuasan Pelanggan Sebagai Perbaikan Mutu Pendidikan - Sari, Dwi Lutfiana (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
Examines the implementation of the Total Quality Management (TQM) concept as an effort to enhance the quality of education in Indonesia, especially in response to customer demands within educational institutions. Despite government efforts to improve educational quality through various policies, significant challenges remain, such as limited access to education, teacher quality, and suboptimal education management. TQM is applied to help educational institutions focus on customer needs, including students, parents, and the community, to provide high-quality services. Through a library research approach, this article analyses the importance of TQM in education as a strategic method to improve service quality and customer satisfaction. The findings are expected to serve as a reference for education practitioners in implementing TQM as an effort to enhance the quality and competitiveness of educational institutions.